Politics of Restructuring and Nation-Building in Nigeria, 1966-2019 - Opone, Paul O. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Agitation for the restructuring of Nigeria has become a topical issue in political discourse in recent times. Day by day, there seems to be a growing consensus in many quarters in Nigeria that the nation needs to be restructured following perceived structural imbalance in the Nigerian federation, which has greatly affected unity and national integration. Against this background, this paper examines such calls for restructuring for the Nigerian federation. The aim is to contribute to the national integration process in Nigeria by finding out whether restructuring will strengthen unity in diversity, or would lead to more diversity. To do this, the paper interacted with the available works on the subject and deployed the historical methods of description and analysis. The paper showed that while the military is credited for preserving Nigeria’s unity, it none the less created a structural imbalance in the federation by emasculating too much power at the centre to the detriment of the federating units. Such a deliberate policy of the military has come to challenge unity in diversity in a democratic dispensation. The conclusion is drawn from the implications for the refusal by the current Nigerian government to commit to restructuring especially the danger it portends for the continued existence of Nigeria as a united country. Keywords: Politics, Restructuring, Nation-building, Federalism, National Integration, Agitations, Unity in Diversity, Stability.